KAWASAN WISATA AIR TERJUN DAIT DI KABUPATEN LANDAK - Windi Guswirno Hedi; Syaiful Muazir; Valentinus Pebriano (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Landak Regency has many natural resources that have the potential to be used as natural tourism objects. One of them is Dait Waterfall which has 7 floors and is located in an unspoiled forest area. The area is often visited by tourists from various regions of West Kalimantan. However, there are several problems related to supporting facilities and infrastructure that are not up to standard for tourism activities, so that the tourism potential is not maximized. For this reason, it is necessary to design a